PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KOTA SALATIGA - Sheyla Hernaning Failashufa; Cicilia Dyah Sulistyaningrum Indrawati; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2021)
The purposes of this study are to find out: 1) the effect of work motivation on job satisfaction of employees; 2) the effect of work discipline on job satisfaction of employees; and 3) the simultaneously effect of work motivation and work discipline on job satisfaction of employees.This study is a quantitative study with a survey method. The population in this study were all employees of The Regional Development Planning Board (BAPPEDA) of Salatiga City, totaling 40 employees. Tis research, the authors use a sample is taken whole from the total population or it’s called sampling jenuh technique. Data collection techniques with questionnaires. IBM SPSS 22.0 has been used in technique data analysis that is multiple linear regression analysis. The results show 1) there was a positive and significant effect of motivation on employee job satisfaction. This is evidenced by thitung > ttabel (3,784 > 2,026) and significance (0,001 < 0,05); 2) there was a positive and significant effect of work discipline on employee job satisfaction. This is evidenced by thitung > ttabel (2,608>2,026) and significance (0,013 < 0,05); 3) there was a positive and significant simultaneously motivation and work discipline on employee job satisfaction. This is evidenced by Fhitung > Ftabel (26,322>3,24). The results of this analysis supported this hypothesis